Study on Structures Incorporated With MR Damping Material Based on PSO Algorithm - Guo, Ying-Qing; Xie, Wen-Han; Jing, Xingjian (Frontiers in Materials, 2019)
The magnetorheological (MR) damping material is a kind of smart shock absorption material, and it can be made into MR dampers for reducing the vibration or dynamic response of structures. During the vibration mitigation control of structures with MR dampers, the displacement and acceleration responses are always concerned firstly because the displacement responses determine the safety of structures and at the same time the acceleration responses determine the comfort level of the human body staying in structures. That means, the control currents choice of MR dampers during vibration process is a multi-objective optimization control problem. In this paper, the particle swarm optimization (PSO) algorithm is developed to control the displacement and acceleration responses simultaneously. Numerical analysis for a five-floor structure with one MR damper installed on each floor is carried out. Simulation results of the PSO control structure are compared with those of passive control (including the On-control and the OFF-control) structures and the uncontrolled structure. Analysis results demonstrate that the PSO algorithm can reduce the displacement responses of the structure obviously, at the same time, it can reduce the acceleration responses of the structure to a certain extent. Furthermore, the PSO algorithm reduces seismic responses of structures more effectively than those of passive control structures.